Territorial Transformations and Inequalities in the Rural Habitat of Northwestern Córdoba - Cejas, Noelia (2025)
The persistent inequalities surrounding access and permanence of communities in the peasant rural habitat in northwestern Córdoba lead us to inquire about the different territorial transformations carried out by the State and the market which, in recent decades, have accentuated historical inequities. The meta-discourse of development permeates the definitions from which actions are deployed in the province of Córdoba; the production of space possesses singularities and historical processes, and its analysis allows us to note that dichotomous thinking, expressed in urban-rural, backwardness-progress, etc., pairs, configures the silencing of territorialized knowledge and forms of inhabiting adjusted to vernacular worldviews. To address these processes, we recognize different levels of analysis that we propose to order as macro and micro-political scales of the rural habitat. Although both scales constitute analytically differentiable aspects, they are presented to us as articulated in the experiences.